2020
DOI: 10.1186/s12861-020-00228-y
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of SNRNP200 inhibits the osteo−/dentinogenic differentiation and cell proliferation potential of stem cells from the apical papilla

Abstract: Background Tissue regeneration mediated by mesenchymal stem cells (MSCs) is deemed a desirable way to repair teeth and craniomaxillofacial tissue defects. Nevertheless, the molecular mechanisms about cell proliferation and committed differentiation of MSCs remain obscure. Previous researches have proved that lysine demethylase 2A (KDM2A) performed significant function in the regulation of MSC proliferation and differentiation. SNRNP200, as a co-binding factor of KDM2A, its potential effect in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 52 publications
1
7
0
Order By: Relevance
“…In terms of osteogenesis, it has been previously reported that SNRNP200 knockdown can inhibit the osteogenic/odontogenic differentiation of SCAPs (Su et al, 2020). In this study, we found that knockdown of SNRNP200 inhibited the ALP activity and mineralization ability in DPSCs, indicating that SNRNP200 might promote the odontogenic differentiation of DPSCs.…”
Section: Discussionsupporting
confidence: 52%
“…In terms of osteogenesis, it has been previously reported that SNRNP200 knockdown can inhibit the osteogenic/odontogenic differentiation of SCAPs (Su et al, 2020). In this study, we found that knockdown of SNRNP200 inhibited the ALP activity and mineralization ability in DPSCs, indicating that SNRNP200 might promote the odontogenic differentiation of DPSCs.…”
Section: Discussionsupporting
confidence: 52%
“…In addition, SNRNP200 is also involved in the process of mammalian cell cycle ( Ehsani et al, 2013 ). In terms of osteogenesis, it has been previously reported that SNRNP200 knockdown can inhibit the osteogenic/odontogenic differentiation of SCAPs ( Su et al, 2020 ). In this study, we found that knockdown of SNRNP200 inhibited the ALP activity and mineralization ability in DPSCs, indicating that SNRNP200 might promote the odontogenic differentiation of DPSCs.…”
Section: Discussionmentioning
confidence: 99%
“…MSCs proliferation can also be consistently inhibited by the knockdown of SNRNP200, a co-binding factor of KDM2A, by blocking MSCs in the G2/M and S phases of the cell cycle. Deleting SNRNP200 upregulated CDKN1A and p53 but downregulated CDK1, CYCB, CYCE, and CDK2 ( 153 ). Pharmacological G9a inhibition significantly enhanced MSCs proliferation ( 154 ).…”
Section: Epigenetic Control Of Mscs In Bone Regenerationmentioning
confidence: 99%